(untitled) (Politeja, 2019)
The Constitutional Role of the President of the Republic of Poland in the Context of Membership of the European Union The article presents a synthetic analysis of issues related to the constitutional position of the President of the Republic of Poland in constitutional and institutional order in the context of Poland’s membership in the structures of the European Union. The text mentions the basics of not only legal but also functional elements of the constitutional system. The purpose of this article is also to indicate how much the constitutional model of the executive bodies is sufficient to resolving problematic political issues when there is a particular kind of relationship between the head of state and the government administration.